An Unusual Protector-Protégé Strategy for the Biosynthesis of Purine Nucleoside Antibiotics. Issue 2 (16th February 2017) - Wu, Pan; Wan, Dan; Xu, Gudan; Wang, Gui; Ma, Hongmin; Wang, Tingting; Gao, Yaojie; Qi, Jianzhao; Chen, Xiaoxia; Zhu, Jian; Li, Yong-Quan; Deng, Zixin; et al.
Summary: Pentostatin (PTN, deoxycoformycin) and arabinofuranosyladenine (Ara-A, vidarabine) are purine nucleoside antibiotics used clinically to treat hematological cancers and human DNA virus infections, respectively. PTN has a 1, 3-diazepine ring, and Ara-A is an adenosine analog with an intriguing epimerization at the C-2′ hydroxyl group. However, the logic underlying the biosynthesis of these interesting molecules has long remained elusive. Here, we report that the biosynthesis of PTN and Ara-A employs an unusual protector-protégé strategy. To our surprise, we determined that a single gene cluster governs PTN and Ara-A biosynthesis via two independent pathways. Moreover, we verified that PenB functions as a reversible oxidoreductase for the final step of PTN. Remarkably, we provided the first direct biochemical evidence that PTN can protect Ara-A from deamination by selective inhibition of the host adenosine deaminase. These findings expand our knowledge of natural product biosynthesis and open the way for target-directed genome mining of Ara-A/PTN-related antibiotics. Graphical Abstract: Highlights: A single gene cluster is responsible for pentostatin and vidarabine biosynthesis Pentostatin and vidarabine arise from independent biosynthetic pathways PenB functions as a reversible oxidoreductase for the final step of pentostatin Pentostatin protects vidarabine by selective inhibition of adenosine deaminase Abstract : Wu et al. discovered that a single gene cluster is employed in two independent pathways for the biosynthesis of pentostatin and vidarabine and uncovered a protector-protégé strategy. The pentostatin pathway involves a final, reversible dehydrogenation step. These findings expand our knowledge of nucleoside antibiotics biosynthesis.